Analisis Pemilihan Platform E-Commerce Berdasarkan Preferensi Pengguna dengan Metode SAW - zulkarnain zul (Universitas Baturaja, 2025)
The advancement of information technology has significantly influenced consumer behavior, particularly in online shopping activities. E-commerce platforms have become the primary choice for the public due to their convenience, time efficiency, and wide range of product offerings. However, the abundance of available platforms can make it difficult for users to determine which platform best suits their preferences and needs. This study aims to analyze and determine the most suitable e-commerce platform based on user preferences using the Simple Additive Weighting (SAW) method. SAW is chosen for its ability to provide objective evaluation results by assigning weights to each criterion and calculating the preference values of alternatives. In this study, five platforms—Shopee, Tokopedia, Lazada, Bukalapak, and Danviashop—are evaluated based on four key criteria: product quality, trust level, price, and ease of use. Data were collected through a combination of observation and questionnaire distribution to active e-commerce users. The analysis results show that Shopee and Danviashop received the highest scores, each with a value of 0.97, indicating their advantages in terms of product quality and user convenience. Tokopedia and Lazada followed with scores of 0.88, while Bukalapak received the lowest score of 0.83. This study confirms the effectiveness of the SAW method in multi-criteria decision-making processes and provides meaningful insights to help users make more accurate and objective platform selections. The findings may also serve as valuable input for business stakeholders and platform developers seeking to improve service quality.